A importância da imigração italiana no desenvolvimento econômico do bairro Santana em Rio Claro (SP) - Prado, Thiago Willian [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
At the end of the 19th century and beginning of the XX century, Brazil received thousands of Italian families who settled in the Brazilian land, mainly in the Southeast and South regions of Brazil. Within the Southeast Region, São Paulo was the state that received the most number of families from Italy who settled on the coffee farms in substitution of the slave labor that suffered its decay with the several laws elaborated to end this type of exploitation. During this period (late nineteenth and early twentieth) the Rio Claro region had its importance in the coffee sector, therefore, many families came from the port of Santos to the farms of the region and helped in the development of the city of Rio Claro. The Santana district, formed mostly by Italian families, stands out for its dynamism in the Rio-Clarense municipality. This research aims to demonstrate the importance of these Italian families in the economic development of the Santana district

O Brasil recebeu no final do século XIX e início do XX milhares de famílias italianas que se estabeleceram em território brasileiro, sobretudo, nas regiões Sudeste e Sul do Brasil. Dentro da Região Sudeste, São Paulo foi o estado que mais recebeu essas famílias oriundas da Itália que se estabeleceram nas fazendas de café em substituição da mão-de-obra escrava que sofria sua decadência com as diversas leis elaboradas para acabar com esse tipo de exploração. Nesse período (final de XIX e início do XX) a região de Rio Claro tinha sua importância no meio cafeeiro, portanto, muitas famílias vinham do porto de Santos para as fazendas da região e ajudaram no desenvolvimento da cidade de Rio Claro. O Bairro Santana formado, majoritariamente, por famílias italianas se destaca pelo seu dinamismo no município rio-clarense. Essa pesquisa tem por objetivo demonstrar a importância dessas famílias italianas no desenvolvimento econômico do Bairro Santana
Keywords: Migração; Desenvolvimento econômico; Trabalhadores do cultivo do café; Rio Claro (SP); Rio Claro (SP) - Séc. XIX; Rio Claro (SP) - Séc. XX; Brasil; Italia